Do Islamic Microfinance Practise Descrease the Level of Three Aspects of Poverty - wulandari, ries; Dzakiroh, Husna (IQTISHADIA, 2019)
Islamic microfinance institutions such as Baitu Tamkin is one of Koperasi Syariah at Lombok Timur practising islamic value. In practising islamic value, Baitu Tamkin insert this value in line with three aspect including commercial finance, social aspect, and spiritual awareness. But the evaluation of this islamic microfinance practise has not been conducted yet.  Therefor we conducted a research to evaluate the curent impact of this program wheter there was improvement and how the conditions of poverty in the member self before and after taking part in empowerment programs on Baitut Tamkin.   Poverty condition that we observed not only financial aspect but also social and spiritual aspect. This research used parametric including Multiple Linear regression, a simple Linear Regression, t-test and non parametric test using Wilcoxon test. We conclude that the level of poverty at local region decreased at  three aspects but with various condition.  First, the islamic commercial financing significantly increasing their member’s montly liquidity but do not significantly increase their member’s housing condition. Second, the social condition of member showed that after being a member they create more friendly environment and helping each other. But there is no impact at “become islamic role model’ or and uswah al-hasanah. Third, spiritual awareness of member increased after they could practising some muamalah based on verses and hadith at muamalah. Number of member that moving from poor condition to empowered condition showed positive trend.